2014 Tenth International Conference on Signal-Image Technology and Internet-Based Systems 2014
DOI: 10.1109/sitis.2014.68
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolutionary Dynamics in Social Networks: A Case Study of Twitter

Abstract: Complex networks often exhibit co-evolutionary dynamics, meaning that the network topology and the state of nodes or links are coupled, affecting each other in overlapping time scales. We focus on the co-evolutionary dynamics of online social networks, and on Twitter in particular. Monitoring the activity of thousands of Twitter users in real-time, and tracking their followers and tweets/retweets, we propose a method to infer new retweet-driven follower relations. The formation of such relations is much more l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
(23 reference statements)
2
17
0
Order By: Relevance
“…From Figs 3 and 4 , we can easily find that the probability of follow relation created is increasing with the increase of observation number. Comparing with similar studies in Twitter, our conclusion is contrary to the conclusion in 12 , however, is same with conclusions in 13 14 15 . We consider that Zhu et al 12 only examined the relationship between how often a user v received a specific user @CARightToKnow and the average probability that v followed @CARightToKnow in return.…”
Section: Information Diffusion and Link Predictionsupporting
confidence: 81%
See 2 more Smart Citations
“…From Figs 3 and 4 , we can easily find that the probability of follow relation created is increasing with the increase of observation number. Comparing with similar studies in Twitter, our conclusion is contrary to the conclusion in 12 , however, is same with conclusions in 13 14 15 . We consider that Zhu et al 12 only examined the relationship between how often a user v received a specific user @CARightToKnow and the average probability that v followed @CARightToKnow in return.…”
Section: Information Diffusion and Link Predictionsupporting
confidence: 81%
“…Zhou et al 12 found that exposing the same user multiple times does not necessarily increase the probability a new link will form, and they also proposed a visibility-based model for link prediction. Myers et al 13 , Weng et al 14 and Antoniades et al 15 also focused on the same problem, but got a different conclusion that that repeated exposure to contents posted by a user increases the probability of following that user. Farajtabar et al 16 proposed a model for simulating diffusion and network events form the co-evolutionary dynamics which can be used to predict links.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper is an extended version of work published in [6]. We extend our previous work by examining a second instance of co-evolutionary dynamics on Twitter, namely the possibility of an unfollow event to occur.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover, network structures and information diffusion could also be mutually determined. For example, individuals are inclined to follow new users who they have retweeted on Twitter (Antoniades & Dovrolis, 2015). We are uncertain about to what extent mutual causality can bias our findings.…”
Section: Discussionmentioning
confidence: 99%